2015
DOI: 10.3126/kumj.v13i1.13757
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Other Risk Factors among Stroke Patients

Abstract: Background Stroke is common neurological problems in Nepal. The common risk factors for stroke are age, hypertension, diabetes, dyslipidemia and atrial fibrillation. Vitamin D is an emerging risk factors for cardio-cerebrovascular disease.Objective This study is to find out Vitamin D and risk factors in stroke patient in Nepalese population.Method We reviewed the record of 281 stroke patients, admitted to Neurology ward of College of Medical Sciences, Bharatpur, Nepal from 1st January to 31st December 2013.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
6
4
0
Order By: Relevance
“…However, the above studies had limited representation of the individuals from China. In our study, we further confirmed patients with SVD were correlated with the deficiency of 25(OH)D. Our study was in line with the former studies in different race such as in in Nepalese population or India [11,[26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…However, the above studies had limited representation of the individuals from China. In our study, we further confirmed patients with SVD were correlated with the deficiency of 25(OH)D. Our study was in line with the former studies in different race such as in in Nepalese population or India [11,[26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we further confirmed patients with SVD were correlated with the deficiency of 25(OH)D . Our study was in line with the former studies from different races including in Nepal, India, Iran and Italy [14,[30][31][32][33][34][35][36]. [37].…”
Section: Discussionsupporting
confidence: 91%
“…However, the above studies had a limited representation of individuals from China. In our study, we further confirmed patients with SVD were correlated with the deficiency of 25(OH)D. Our study was in line with the former studies from different races including in Nepal, India, Iran and Italy [15,[31][32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 90%